EUFORIA OTONOMI DAERAH DALAM BINGKAI POLITIKHUKUM PASCA REFORMASI DI INDONESIA - Jamaludin . (UNIVERSITAS ISLAM KADIRI, 2015)
A wave of regional autonomy in Indonesia, which led to the enactment of Law Number 23 of 2004 concerning Local Government and Government Regulation Number 78 of 2007 actually, in principle, as a correction of the weaknesses of Law Number 22 of 1999 and Government Regulation No. 129 of 2000 by tightening the requirements regional expansion. But in its implementation, the Government Regulation Number. 78 of 2007 is not effective, due to the politicization of interest. Legal product is basically a political product, but many aspects people interest must necessarily remain the main spirit of the laws themselves. For the essential decentralization and regional autonomy are to the welfare of the community, shortening the span of control, and improve public services